A rare cause of cardiogenic shock: Variant angina - SÜNBÜL, MURAT; YEŞİLDAĞ, OSMAN (My University, 2014)
Variant angina (VA) is a clinical syndrome caused by spontaneous vasospasm of the epicardial coronary artery which is characterized by episodes of angina. Endothelial dysfunction and neurohormonal hyperactivity are important factors in pathogenesis of VA. Although patient prognosis is good, VA may be one of the reasons of sudden cardiac death (SCD) in case of persistent ST segment elevation and malignant arrhythmias. Therefore, early treatment of VA is crucial for prevention of malignant arrhythmias and SCD. In this case report we describe a case of VA presented with cardiogenic shock and malignant ventricular arrhythmia. © 2014, SAGE Publications. All rights reserved.
Keywords: cardiogenic shock; coronary vasospasm; variant angina